195k views
1 vote
Please help D: Given f (x) = 3 x minus 1 and g (x) = 2 x minus 3, for which value of x does g (x) = f (2)?

x = 3/2

x = 2

x = 5/2

x = 4

User Birb
by
5.2k points

1 Answer

2 votes

Answer: D. x = 4

===============================================

Step-by-step explanation:

First compute f(2)

f(x) = 3x-1

f(2) = 3(2) - 1 ... replace every x with 2; use PEMDAS to simplify

f(2) = 6 - 1

f(2) = 5

When we say g(x) = f(2), we really mean g(x) = 5

g(x) = 2x-3

2x-3 = g(x)

2x-3 = 5 .... plug in g(x) = 5

2x-3+3 = 5+3 ... add 3 to both sides

2x = 8

2x/2 = 8/2 ... dividing both sides by 2

x = 4

User Xbakesx
by
5.1k points